Vertentes Utópicas em The Hobbit - Silva, Jorge Bastos da (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2020)
This article offers a commentary on J. R. R. Tolkien’s The Hobbit (1937) by way of a contrast between two utopian paradigms: the quest romance and the ideal city. The analysis emphasizes the significance of the former as an inducement to critical awareness concerning the problem of good and evil, in a manner which suggests the possibility of every individual’s commitment to fruitful action.